Russian Federation : Financial Sector Assessment Program: Technical Note-Bank Resolution and Crisis Management Framework. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for the Russian Federation in the areas of bank resolution and a crisis management framework. The findings reveal that the experiences of past financial crises have strengthened the Russian bank resolution framework. The resolution framework has been effective in preserving financial stability. Since January 2014, 28 banks have been placed in open bank resolution, and three were resolved by purchase and assumption transactions. The effectiveness of bank resolution could be improved. Introduction of the full range of resolution powers and safeguards recommended by the Financial Stability Board Key Attributes would improve the framework's effectiveness.